2013
DOI: 10.1155/2013/261054
|View full text |Cite
|
Sign up to set email alerts
|

Actin Is a Target of T-Cell Reactivity in Patients with Advanced Carotid Atherosclerotic Plaques

Abstract: Atherosclerosis is a chronic inflammatory disease of the arterial wall associated with autoimmune reactions. In a previous study, we observed the presence of actin-specific antibodies in sera from patients with carotid atherosclerosis. To extend our previous results we evaluated the possible role of actin as antigenic target of cell-mediated immune reactions in carotid atherosclerosis. Peripheral blood mononuclear cells (PBMC) from 17 patients and 16 healthy subjects were tested by cell proliferation assay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Moreover, reflective of plaque-directed immunity, different auto-antigens are identified targets of immune responses in atherosclerosis. Oxidized low density lipoprotein (oxLDL) is the most well described 19 , but Tcells isolated from patients with advanced atherosclerosis also respond to F-actin, a known target in necrosis-associated cross-presentation 20 21 . Lastly, a recent study has demonstrated that cytotoxic CD8 + Tcells promote development of a vulnerable atherosclerotic plaque in mice, implicating cytolytic Tcell immunity in plaque destabilization 22 .…”
mentioning
confidence: 99%
“…Moreover, reflective of plaque-directed immunity, different auto-antigens are identified targets of immune responses in atherosclerosis. Oxidized low density lipoprotein (oxLDL) is the most well described 19 , but Tcells isolated from patients with advanced atherosclerosis also respond to F-actin, a known target in necrosis-associated cross-presentation 20 21 . Lastly, a recent study has demonstrated that cytotoxic CD8 + Tcells promote development of a vulnerable atherosclerotic plaque in mice, implicating cytolytic Tcell immunity in plaque destabilization 22 .…”
mentioning
confidence: 99%
“…The change of actin microfilaments has shown a strong relationship with the reduction of stress fibers and dysfunctional adhesion, causing the accumulation of immune cells and the formation of atherosclerotic plaque (33,34). Recently studies have also suggested that actin is a vital autoantigen target that mediates the autoimmune process of plaque formation and stability in patients with carotid atherosclerosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Zhao et al showed on animal models that IL-4 might induce macrophages to take on an M2 phenotype to resolve inflammation, thereby protecting against atherosclerosis [45]. In 2013, Profumo found no significant difference in IL-4 levels in patients with carotid atherosclerosis compared to healthy subjects [23]. Recent studies found M1 macrophages to be associated with unstable plaques and M2 macrophages with stable plaques.…”
Section: Il-4mentioning
confidence: 99%
“…IL-4 regulates macrophage polarization to M2 phenotype, which protects against atherosclerosis. Results of studies assessing the concentration of plasma levels of IL-4 in patients with atherosclerosis have been controversial [22,23].…”
Section: Introductionmentioning
confidence: 99%